Melanosis of the Bladder: Possible Pathogenetic Mechanisms - Justin E. Dupey; Sarah J. Wood; Richard Y. Ball (Case Reports in Urology)
Melanin accumulation within the bladder urothelium and/or macrophages in the lamina propria (melanosis of the bladder) is a very rare phenomenon of unknown pathogenesis. Its rarity argues for a complex, likely multifactorial, causation. We describe bladder melanosis developing after Botox therapy in an elderly woman with a history of overactive bladder, treated grade 2 uterovaginal prolapse, and episodes of urinary tract infection and speculate that one factor (probably of many) in its pathogenesis may be a derangement of local neurourothelial interactions.